Censorship in the people's republic of China - Soroka, O.S. (ХНУ ім. В.Н. Каразіна, 2012)
The article deals with the problems of the censorship in the People's Republic of China. Press, television, radio and other mass media are analized. The conclusion is made that censorship has been prevalent in China for centuries.
В статье речь идет о проблемах цензуры в Китайской Народной Республике. Анализируються пресса, телевидение, радио и другие СМИ. Выводы состоят в том, что цензура доминировала в Китае на протяжении столетий.
Keywords: censorship; mass media; press; television; radio